2016
DOI: 10.1016/j.expneurol.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

High frequency oscillations can pinpoint seizures progressing to status epilepticus

Abstract: Status epilepticus (SE) is defined as a seizure lasting more than 5 min or a period of recurrent seizures without recovery between them. SE is a serious emergency condition that requires immediate intervention; therefore, identifying SE electrophysiological markers may translate in prompt care to stop it. Here, we analyzed the EEG signals recorded from the CA3 region of the hippocampus and the entorhinal cortex in rats that responded to systemic administration of 4-aminopyridine (4AP) by generating either isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Indeed, this is a serious emergency condition that requires immediate intervention; therefore, identifying electrophysiological markers of an upcoming status epilepticus may translate in prompt care to stop it. In a recent study, Salami et al (2016) have found that specific interictal oscillations can pinpoint to experimental conditions that are likely to generate either an isolated seizure (Fig. 4A) or to progress to status epilepticus (Fig.…”
Section: Interictal Oscillations As Predictor Of Status Epilepticusmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, this is a serious emergency condition that requires immediate intervention; therefore, identifying electrophysiological markers of an upcoming status epilepticus may translate in prompt care to stop it. In a recent study, Salami et al (2016) have found that specific interictal oscillations can pinpoint to experimental conditions that are likely to generate either an isolated seizure (Fig. 4A) or to progress to status epilepticus (Fig.…”
Section: Interictal Oscillations As Predictor Of Status Epilepticusmentioning
confidence: 95%
“…In a recent study, Salami et al . () have found that specific interictal oscillations can pinpoint to experimental conditions that are likely to generate either an isolated seizure (Fig. A) or to progress to status epilepticus (Fig.…”
Section: Interictal Oscillations As Predictor Of Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation
“…8 As high-frequency activity has been shown to increase prior to seizure onset both clinically and in experimental models, [9][10][11] some have also hypothesized a link between HFOs, the mechanisms of ictogenesis, and preictal brain states. [10][11][12][13][14][15][16][17][18] The existence of a preictal state is still unproven, but growing evidence suggests it is measurable in many patients. [19][20][21] One notable study found differences in preictal electroencephalogram (EEG) occurring even hours before seizure onset.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] A higher number of ictal fast ripples was found in rats with seizures progressing to status epilepticus than in rats with focal seizures. 39 Using intracranial EEG, Schöenberger and coworkers showed that within the same individuals HFO rates were high in seizures that progressed to secondary generalization compared with those that remained focal. 40 This difference between seizure types was visible prior to the clinical occurrence of secondary generalization.…”
Section: High Frequency Oscillations and Seizure Predictionmentioning
confidence: 99%